The Role of Intellectual Capital and Good Corporate Governance Toward Financial Performance - Kartika, Indri; Indriastuti, Maya; Sutapa, Sutapa (Jurnal ASET (Akuntansi Riset), 2021)
The purpose of this study is to analyze and test empirically the variables that affect financial performance. Using 520 manufacturing companies listed on Indonesia Stock Exchange for the period of 2010-2019, all data were processed by using the structural equation modeling analysis. The results of this study explained that intellectual capital and good corporate governance in terms of the board of commissioners have a significant positive effect on financial performance. The existence of intellectual capital and the board of commissioners can improve financial performance, so that manufacturing companies are able to survive and even be stable. The implication of this study is to enrich the literature review and to be used as policy making basis for the government and manufacturing companies. Moreover, it can be a basis for investors to consider an investement